The New book of knowledge. - Grolier Incorporated (Danbury, Conn : Grolier Incorporated, c2002, 2002)
An illustrated encyclopedia with articles on history, literature, art and music, geography, mathematics, science, sports, and other topics. some articles include activities, games, or experiments.
Includes index.
Keywords: Children's encyclopedias and dictionaries; Encyclopedias and dictionaries